2014
DOI: 10.1016/j.breast.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of pure flat epithelial atypia identified on core needle breast biopsy

Abstract: The biology of flat epithelial atypia (FEA) is still being investigated as its presence becomes more frequent on biopsy specimens. FEA is more commonly associated with malignancy when found in association with ADH, ALH or LCIS. Pure FEA is only upgraded to cancer in 3.2% of patients. Surgical excision of pure FEA found on core needle biopsy results in overtreatment in the vast majority of breast patients and may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
2
12
2
Order By: Relevance
“…On literature review, approximately 8% of pure flat epithelial atypia diagnosed on core needle biopsy was upgraded to carcinoma, with a range of 0-21% (Table 7). 19,20,22,24,30,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] In our study, no statistically significant radiologic differences were seen between upgraded and not upgraded flat epithelial atypia core needle biopsy groups; however, residual calcification after biopsy was associated with upgrade. For pure flat epithelial atypia, as stated in the World Health Organization Working Group, careful radiological-pathological correlation is necessary, and in the absence of residual calcifications or other indications for excision, surveillance may be acceptable.…”
Section: Discussioncontrasting
confidence: 66%
“…On literature review, approximately 8% of pure flat epithelial atypia diagnosed on core needle biopsy was upgraded to carcinoma, with a range of 0-21% (Table 7). 19,20,22,24,30,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] In our study, no statistically significant radiologic differences were seen between upgraded and not upgraded flat epithelial atypia core needle biopsy groups; however, residual calcification after biopsy was associated with upgrade. For pure flat epithelial atypia, as stated in the World Health Organization Working Group, careful radiological-pathological correlation is necessary, and in the absence of residual calcifications or other indications for excision, surveillance may be acceptable.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous research suggests that up to 10% of all core needle breast biopsies may have FEA noted by the interpreting pathologist. 2 Our study corroborates these observations. Although studies have evaluated the incidence of breast cancer in women with FEA, 39,40 their applicability relies on the reproducibility of FEA as a diagnostic entity.…”
Section: Discussionsupporting
confidence: 90%
“…2 Each year, 1.6 million breast biopsies are performed on women in the United States, 3,4 suggesting a large number of women will be diagnosed with FEA. The World Health Organization (WHO) established the defining features of FEA in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study of 24 cases showed an upgrade rate of 3.2%. 28 Piubello et al 29 and Noel et al 30 reported no cases with carcinoma on excision in two smaller series in which only the patients with residual suspicious calcifications underwent surgical biopsy for flat epithelial atypia. It must also be noted that all but one of the pre-core biopsy imaging studies in our series were BIRADS-4.…”
Section: Discussionmentioning
confidence: 96%